Comparing South Korea and Italy's healthcare systems and initiatives to combat COVID-19 - Ashwin Palaniappan; Udit Dave; Brandon Gosine (Pan American Health Organization, 2020)
Italy and South Korea have two distinctly different healthcare systems, causing them to respond to public health crises such as the COVID-19 pandemic in markedly different ways. Differences exist in medical education for both countries, allowing South Korean medical graduates to have a more holistic education in comparison to their Italian counterparts, who specialize in medical education earlier on. Additionally, there are fewer South Korean physicians per 1000 people in South Korea compared to Italian physicians per 1000 people in Italy. However, both countries have a national healthcare system with universal healthcare coverage. Despite this underlying similarity, the two countries addressed COVID-19 in nearly opposite manners. South Korea employed technology and the holistic education of its physician community, despite having a smaller proportion of physicians in society, to its advantage by implementing efficacious drive-through centers that test suspected individuals rapidly and with little to no contact with healthcare staff, decreasing the possibility of transmission of COVID-19. Conversely, Italy is presently considered the epicenter of the outbreak in Europe and has recorded the highest death toll of any country outside of mainland China. This is partially due to the reactionary nature of Italy's public health measures compared to South Korea's proactive response. The different healthcare responses of South Korea and Italy can inform decisions made by public health bodies in other countries, especially in countries across the Americas, which can selectively adopt policies that have worked in curtailing the spread of COVID-19 and learn from mistakes made by both countries.